A Novel Mutation of GARS in a Chinese Family With Distal Hereditary Motor Neuropathy Type V - Yu, Xueying; Chen, Bin; Tang, Hefei; Li, Wei; Fu, Ying; Zhang, Zaiqiang; Yan, Yaping (Frontiers in Neurology, 2018)
Glycyl-tRNA synthetase (GARS) gene mutation have been reported to be associated with Charcot-Marie-Tooth disease 2D (CMT2D) and distal hereditary motor neuropathy type V (dHMN-V). Here, we report a novel GARS mutation in a Chinese family with dHMN-V. Clinical, electromyogram, genetic and functional data were explored. The proband was an eleven-year-old girl presented with progressive distal limb muscle weakness and atrophy due to peripheral motor neuropathy for one year. Another 5 members from three successive generations of the family showed similar symptoms during their first to second decades and demonstrated an autosomal dominant inheritance. The results of genetic testing revealed a novel c.383T>G mutation in GARS gene in the affected individuals, showing apparent genetic co-segregation. Further bioinformatic analyses showed that the c.383T > G mutation resulted in L128R alteration in the second functional protein domain, and the mutation site was well conserved among different species. In silico analysis predicted that this mutations probably affected protein function. In vitro, this GARS mutation led to a different protein localization pattern compared with that of the wild-type (WT) enzyme. The study found novel GARS mutation of c.383T > G causing dHMN-V with subcellular localization abnormity in a genetic co-segregation family. These findings broaden the mutational spectrum of GARS .